A paisagem como construção da figura do pai profano e do pai sagrado em Um rio chamado tempo, uma casa chamada terra, de Mia Couto - Pinto, Sandra Fonseca (2016)
The novel Um rio chamado tempo, uma casa chamada terra, Mia Couto, had its first edition published in 2002, for publishing company Caminho, from Portugal. In this novel, the landscape s phenomenology is configured through the perspective of Marianinho s view, narrator character, returning to the island of Luar-do-Chão for the funeral of his grandfather, Dito Mariano, the family patriarch, that is "clinically dead", in other words, neither dead nor alive. The author creates, in this novel, a sacred and mystical universe through dialogues between the characters and the nature elements, considered divinities, and landscapes that are part of this interaction. This work investigates the relationship of the physical, cultural and historical space, with the construction of the image of the profane or holy father, based on landscape studies, constituting in a bibliographical research. The contribution that founded this research are theories of Michel Collot, with the conception of the landscape s phenomenology, the theoretical considerations of Maurice Merleau-ponty, about phenomenology of perception, the notion of space, place and topophilia of Yi-Fu Tuan, the contributions of Georges Gusdorf and Mircea Eliade about the mythical space, as well as the contributions of Tabitha Wittmann and the author Mia Couto about the culture, beliefs and Mozambican customs. The results point to the intense presence of the profane and the sacred in this novel, perceived in landscapes constituted from the perspective of the character of Marianinho, constructed in the mythical space of the literary work, representing the Mozambican culture in relation to the nature and father figure, reflected in the novel